The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1080/00223980.2014.885874
|View full text |Cite
|
Sign up to set email alerts
|

Morningness–Eveningness and Risk Taking

Abstract: Depending on individual differences in biological rhythms and diurnal preferences, people have long been described as either "larks" or "owls." Larks and owls differ greatly in personality aspects, but from the behavioral perspective it is unclear whether they have significant differences in terms of risky behaviors. Whether morning types or evening types are consistently more risk-taking or risk-averse in different domains remains unknown. This study adopted a general American adult sample to systematically i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 47 publications
3
30
5
Order By: Relevance
“…Moreover, our results provide support for previous research showing a link between eveningness and risky behavior in domains other than driving, for example in the financial domain (Wang & Chartrand, 2015). We also show that inclination toward eveningness is associated with more selfreported alcohol use in terms of quantity and frequency, which is consistent with prior research showing that alcohol consumption is more prevalent among evening-type individuals (Adan, 1994;Prat & Adan, 2011;Wittmann et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Moreover, our results provide support for previous research showing a link between eveningness and risky behavior in domains other than driving, for example in the financial domain (Wang & Chartrand, 2015). We also show that inclination toward eveningness is associated with more selfreported alcohol use in terms of quantity and frequency, which is consistent with prior research showing that alcohol consumption is more prevalent among evening-type individuals (Adan, 1994;Prat & Adan, 2011;Wittmann et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Killgore (2007) found that morningness-eveningness scores were not correlated with the scores obtained at the Balloon Analog Risk Task (BART) designed to measure risk-taking in terms of monetary gains. Wang and Chartrand (2015) used a scenario-based risky behavior measurement and found that eveningness was associated with higher risk-taking in terms of investment and gambling, but not in terms of health. Therefore, not only the existing data on the relationship between morningnesseveningness and risk-taking behavior are scarce and inconsistent, but when a link is found it concerns only some specific domains of risk-taking.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations